Intra-natal Care Practices in Rural Areas of Gaya District, Bihar - Suman; Sethy, Ghanashyam; Singh, Chandramani; Jain, Bhavan; Singh Bhadoria, Ajeet (Indian Journal of Community Health, 2023)
Context: Antenatal care (ANC) effectively reduces infant and maternal mortality rates mainly by promoting institutional deliveries. In view of this, the Government of India introduced Janani Suraksha Yojna (JSY) in 2005 and Janani Shishu Suraksha Karyakram (JSSK) in 2011. Aims: To estimate the proportion of home and institutional deliveries in the district, assess the impact of JSK and JSSY on institutional deliveries, and identify the different intranatal care providers. Settings and Design: This cross-sectional study was conducted in the Gaya district, Bihar. A total of 657 females of the reproductive age group (15-49 years) were included in the study. Methods and Material: Predesigned, pre-tested & semi-structured questionnaire was used to collect information on place of delivery, type of delivery, knowledge regarding JSY and JSSK schemes and source of information Statistical analysis used: Data was entered into excel sheets and analyzed using SPSS version 23 utilizing appropriate statistical methods. Results: Out of 519 deliveries, 63% were institutional and 37% were home deliveries. About 91 and 11.4% of respondents were aware of JSY and JSSK schemes. There was a significant association between those who opted for institutional delivery and awareness regarding JSY and JSSK services. Conclusion: Despite awareness and running of various government programs, the percentage of institutional deliveries is still less. An increase in institutional deliveries at primary care level through JSY and JSSK will not only decrease the Out of Pocket expenditure of the population but also help build faith in the government health facilities.